Study on Intermolecular Interaction between Chlorpheniramine and 1-Ethanol at Various Temperatures - Sampandam Elangovan; Tilahun Diriba Garbi; Ponnusamy Thillaiarasu (Recent Trends in Chemical and Material Sciences Vol. 2, 2021)
At temperatures of 303K, 308K, and 313K, the Density (\(ρ\)), viscosity (\(η\)) and ultrasonic velocity (U) of chlorpheniramine with 1-ethanol solutions were measured. Various physicochemical parameters, such as adiabatic compressibility (\(β\)), free length (Lf), free volume (Vf), viscous relaxation time (\(τ\)) and Gibbs free energy (\(\)G) can be obtained via systematic measurements. The objective of the present study is to analyse the intermolecular interaction between the selected liquid system. Further, determine the changes in the interactions with the various temperatures. From the deviations of the excess values,analyse the type of interactions between the amine group present in the chlorpheniramine and the hydroxyl group of the 1-ethanol in the liquid mixtures.The intermolecular interactions are used to calculate and reveal the deviations of such quantities from their ideal values.To validate the calculations, the standard deviations and coefficients of Redlich Kister polynomials of excess quantities are calculated. These findings indicate the existence of intermolecular interactions and their strength with temperatures of 303K>308K>313 K.